51.3k views
2 votes
I need this question to be answer asap

I need this question to be answer asap-example-1

2 Answers

3 votes
Since p(x) = r(x) - c(x), we can plug in r(x) and c(x) to find p(x).
p(x) = 11x - (6x + 20)
Make sure that your problem is subtracting all of c(x) and distribute the subtraction.
p(x) = 11x - 6x - 20
p(x) = 5x - 20
After simplifying, the final answer is D.


User EvilZebra
by
5.0k points
5 votes
If r(x)= 11x, and c(x)=6x +20, then just put that into the equation.
So instead of p(x) = r(x) - c(x)
I would be p(x) = 11x - 6x + 20
Now solve.
p(x) = 5x + 20 is your final answer, so A.
User WebSeed
by
6.1k points